2013
DOI: 10.1155/2013/956397
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Shen-Yuan-Dan, a Traditional Chinese Medicine, against Myocardial Ischemia/Reperfusion InjuryIn VivoandIn Vitro

Abstract: Objectives. The study was to investigate the effects and mechanisms of Shen-Yuan-Dan (SYD) pharmacological postconditioning on myocardial ischemia/reperfusion (I/R) injury. Methods. In the in vivo experiment, myocardial injury markers and histopathology staining were examined. In the in vitro experiment, cell viability and cell apoptosis were, respectively, detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays and Hoechst 33342 fluorochrome staining. The protein expressions of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…These data suggest that the PI3K/Akt/mTORC1 signaling pathway effectively function following SYDC and inhibit the accumulation of lipids in macrophages by enhancing autophagy. Interestingly, our previous study also demonstrated that SYDC prevents the development of atherosclerosis and inflammatory reaction by inhibiting the activation of PI3K/Akt/NF-κB signaling pathway (Zhou et al, 2017), while another previous study also demonstrated that SYDC protects ischemic myocardium from ischemia-reperfusion injury and inhibits cell apoptosis in cardiomyocytes, and the mechanism underlying the cardioprotective effects is associated with activation of the PI3K/Akt pathway (Liu et al, 2013). Therefore, we speculate that PI3K/Akt may be a key signaling pathway for the cardiovascular protective effects of SYDC treatment.…”
Section: Discussionmentioning
confidence: 94%
“…These data suggest that the PI3K/Akt/mTORC1 signaling pathway effectively function following SYDC and inhibit the accumulation of lipids in macrophages by enhancing autophagy. Interestingly, our previous study also demonstrated that SYDC prevents the development of atherosclerosis and inflammatory reaction by inhibiting the activation of PI3K/Akt/NF-κB signaling pathway (Zhou et al, 2017), while another previous study also demonstrated that SYDC protects ischemic myocardium from ischemia-reperfusion injury and inhibits cell apoptosis in cardiomyocytes, and the mechanism underlying the cardioprotective effects is associated with activation of the PI3K/Akt pathway (Liu et al, 2013). Therefore, we speculate that PI3K/Akt may be a key signaling pathway for the cardiovascular protective effects of SYDC treatment.…”
Section: Discussionmentioning
confidence: 94%
“…With the development of thrombolysis, percutaneous transluminal coronary angioplasty and coronary artery bypass grafting, myocardial IR injury has become the main obstacle in obtaining the optimal therapeutic effect from ischemic heart disease during reperfusion treatment ( 28 ). Following myocardial IR therapy, the heart is confronted with further injury through ventricular remodeling ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese cockroach, Eupolyphaga sinensis (Corydiidae), is a key ingredient in a number of traditional Chinese medicinal products including Shu-Mai Tang, Dahuang Zhechong pill, Shensong Yangxin capsule, Shen-Yuan-Dan, Yi Guan Jin and Yaotongning 131 , 132 , 133 , 134 , 135 , 136 . Shu-Mai Tang is prescribed for the treatment of ischemic heart disease and was found to have a therapeutic effect against inflammation-induced myocardial fibrosis leading to the attenuation of left ventricular remodeling and improved cardiac function 131 .…”
Section: Blattodea (Cockroaches and Termites)mentioning
confidence: 99%
“…The Chinese herb modified Yi Guan Jian is an effective regimen that is usually used in outpatients with chronic liver diseases such as fibrosis and cirrhosis 134 . Shen-Yuan-Dan is used for the treatment of ischemic heart disease, proven to relieve angina and reduces cardiac dysfunction 135 Traditional Chinese medicine Yaotongning Capsule is a common remedy to treat rheumatism in China and possesses diverse biological activities including anti-inflammation 136 .…”
Section: Blattodea (Cockroaches and Termites)mentioning
confidence: 99%